Survey and Mapping of P Nutrient Status on Paddy Land in Aek Simare Irrigation Area, Laguboti District, Toba Samosir Regency, Northern of Sumatera, Indonesia - Sari, Kemala; Supriadi,; Siregar, Ameilia Zuliyanti; Sibarani, Muchtar Josua (Jurnal Online Pertanian Tropik, 2020)
The research aims to a mapping of nutrient status available phosphate and total phosphate in the Aek Simare Irrigation Area Laguboti District Toba Samosir Regency. This research was conducted at the Testing Laboratory of Agricultural Technology Research Center in North Sumatera Province. Which began in Mey to June 2019. The method used is the Free Grid Survey detailed level survey and analysis of nutrient data available phosphate by Bray I method, total phosphate by acid destruction method, and then interpret to the map nutrient status. The result of research showing that status available phosphate classified by 3 statuses such as medium (3,99 ha), high (44,26 ha), and very high (71,75 ha). Total phosphate classified in 4 nutrient status such as low (0,004 ha), medium (67,37 ha), high (45,316 ha) and very high (7,31 ha). Available phosphate and total phosphate are very related to increasing rice production in the Aek Simare Irrigation Area Laguboti District Toba Samosir Regency, Northern of Sumatra, Indonesia REFERENCES BPS Toba Samosir. 2018. Laguboti Subdistrict in Figures 2018. Central Bureau of Statistics of Toba Samosir Regency. De Datta, S.K., Buresh, R.J., Mamaril, C.P. 1990. Increasing Nutrient Use Efficiency in Rice with Changing Needs. Kluwer Academic Publishers. Netherland. Center for Soil and Agro-Climate Research (PUSLITANAK). 1983. Assessment Criteria of Soil Chemical Properties. Center for Soil and Agro-climate Research. Bogor Agriculture Department. 2007. References Determination of Fertilizer Recommendations N, P, and K on Specific Rice Fields Location. As an Appendix of Permentan Number40 / Permentan / OT.140 / 04/2007. Sanchez, P. A. 1993. Nature and Tropical Management 2. Translation of Amir Hamzah. ITB. Bandung. Agricultural Land Resources. Bogor, 30 November - 1 December 2010. Husnain. 2010. Loss of Nutrients Due to Burning Rice Straw and Potential of Environmental Pollution. Soil Research Institute. Published Paper at the Proceedings of the National Seminar. Soil Research Institute. Published Paper at the Proceedings of the National Seminar Agricultural Land Resources. Bogor, 30 November - 1 December 2010.